2018
DOI: 10.1016/j.jnutbio.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exercise protects mouse offspring from high-fat-diet-induced type 2 diabetes risk by increasing skeletal muscle insulin signaling

Abstract: Paternal obesity increases, while paternal exercise decreases, offspring obesity and type 2 diabetes (T2D) risk; however, no studies have determined whether a paternal high-fat (HF) diet and exercise interact to alter offspring body weight (BW), adiposity and T2D risk. Three-week-old male C57BL/6 mice were fed a normal-fat (NF) diet (16% fat) or an HF diet (45% fat) and assigned to either voluntary wheel running exercise or cage activity for 3 months prior to mating with NF-diet-fed dams. After weaning, male o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Paternal RT did not result in decreased glucose AUC. Krout et al [11] showed that paternal exercise was protective against insulin resistance by increasing the expression of insulin signaling markers in skeletal muscle resulting in normal T2D risk in offspring. The difference between the present study and Krout et al [11] is the utilization of animals from different species.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
See 2 more Smart Citations
“…Paternal RT did not result in decreased glucose AUC. Krout et al [11] showed that paternal exercise was protective against insulin resistance by increasing the expression of insulin signaling markers in skeletal muscle resulting in normal T2D risk in offspring. The difference between the present study and Krout et al [11] is the utilization of animals from different species.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Krout et al [11] showed that paternal exercise was protective against insulin resistance by increasing the expression of insulin signaling markers in skeletal muscle resulting in normal T2D risk in offspring. The difference between the present study and Krout et al [11] is the utilization of animals from different species. The C57BL/6J lineage mice respond more pronouncedly to HF diet, which can facilitate insulin resistance when compared to Wistar rats [50].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicates that voluntary paternal exercise (running wheel) suppresses the detrimental effects of paternal HF diet on offspring, reducing the harmful effects on glucose tolerance, fat mass and glucose uptake in different skeletal muscles (Stanford et al, 2018). Krout et al (2018) demonstrate that paternal exercise (2 weeks of wheel running) increases the expression of insulin signaling pathways in offspring skeletal muscle, what can be an important tool to prevention type 2 diabetes. Although highly significant, the authors did not strictly manipulate training variables (duration, intensity, rest interval, training volume), which could amplify the understanding of exercise dose on metabolic variables, and tendon offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Ancestral environmental conditions can elicit lifelong effects on the offspring physiology, including increased susceptibility to the obesity and metabolic disorders development (Krout et al, 2018;Winther et al, 2018;Glendining and Jasoni, 2019). Although detrimental effects of maternal obesity during perinatal periods on adiposity and metabolic function in offspring are well established, paternal lifestyle may also influence offspring developmental outcomes.…”
Section: Introductionmentioning
confidence: 99%